Assembly of Captive European Nations : second session, September 1955 - November 1956 : organization, resolutions, reports. (New York : Assembly of Captive European Nations (ACEN), 1957)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: anticommunisme; Oost-Europa.